Optimal treatment sequencing of abiraterone acetate plus prednisone and enzalutamide in patients with castration-resistant metastatic prostate cancer: A systematic review and meta-analysis. (February 2021) - Cassinello, J.; Domínguez-Lubillo, T.; Gómez-Barrera, M.; Hernando, T.; Parra, R.; Asensio, I.; Casado, M.A.; Moreno, P.
Highlights: Efficacy assessment of treatment sequences based on AAP and ENZ in mCRPC patients. AAP-ENZ sequence showed a statistically significant longer PSA-PFS than ENZ-AAP. Literature revealed favourable results in terms of PFS and PSA levels for AAP-ENZ. Clinical efficacy of AAP administered as the first-line treatment in mCRPC patients. Abstract: Purpose: To evaluate the impact of the hormonal treatment sequencing including abiraterone acetate plus prednisone (AAP) and enzalutamide (ENZ) in mCRPC, and determine which sequence provides more benefits for patients. Methods: Studies published in English between 1 January 2013 and 30 September 2017 were identified in PubMed and EMBASE electronic databases. Studies assessing the efficacy of treatment sequences, based on AAP and ENZ, in mCRPC patients, were eligible for analysis. Results: Seventeen studies met the inclusion criteria. Two assessed both treatment sequences AAP → ENZ and ENZ → AAP; it was found that sequence of AAP → ENZ showed a statistically significantly longer PSA-PFS than the observed in ENZ → AAP (pooled HR: 0, 54; 95% CI; 0, 36–0, 82; p < 0, 05 ). The nine studies analysing Doc → AAP → ENZ sequence, revealed favourable results in terms of PFS. The 5 studies which analysed AAP → ENZ sequence, show a decrease in PSA levels ≥ 50% in 11–41% of patients treated with enzalutamide after previous treatment with AAP. In the two studies that analysed the Doc → ENZ → AAP sequence, PSA response rates were much lower than those reported with Doc → AAP → ENZ, with decreases in PSA ≥ 30 of 3–18% and PSA ≥ 50 of 8–11%. Conclusion: Significant clinical efficacy of AAP administered as the first-line treatment in mCRPC patients followed by enzalutamide, delaying disease progression, compared with the ENZ → AAP sequence. However, more studies and randomized trials are needed, to validate the best treatment sequencing.